Investigating the Adoption of Metaverse-Based Immersive Learning in TESOL - Saja Wardat; Mohammed Akour (Emerging Science Journal, 2024)
This study investigates the adoption of Metaverse-based immersive learning in Teaching English to Speakers of Other Languages (TESOL), an area that has been understudied and lacks an understanding of factors influencing the acceptance of this digital platform. In contrast to traditional mobile or e-learning, the Metaverse facilitates all sorts of unique immersive experiences including virtual simulations and cultural dialogues that can aid your process for language acquisition and cultural understanding. However, its reception in the field of TESOL is yet to be substantiated through empirical evidence. The present study explores the effects of constructs such as Perceived ease of use (PEU), Perceived usefulness (PUS), Attitude (ATT), Subjective norm (SBN) and Perceived behavioural control (PBC) on students' Intention to Use Metaverse (IUM) in TESOL context. Data collected from 736 university students in Jordan were analyzed using structural equation modelling (SEM) with a combined Technology Acceptance Model (TAM) and Theory of Planned Behavior (TPB) framework. Results indicate that in terms of direct effects, PEU strongly influences ATT (β = 0.566) and SBN (β = 0.448), whereas PUS regulates ATT (β = 0.514) and SBN (β= 0.482). Path coefficients for the predictive factors of IUM”ATT, SBN, and PBC were 0.326, 0.641, and 0.516 respectively. A J48 decision tree validated by machine learning was able to predict 91.22% of IUM with good accuracy. The results reveal that Metaverse-based TESOL has gradually become part of student habits despite their limited access to technology. The findings of the study assist in improving TESOL curricula and developing informed policies that recommend immersive language learning. Doi: 10.28991/ESJ-2024-SIED1-023 Full Text: PDF